Typologies of Pondok Pesantren in Indonesia and Malaysia: A Comparative Analysis - Hendi Sugianto; Syarof Nursyah Ismail; Kusaeri Kusaeri; Evi Fatimatur Rusydiyah (STAI Hubbulwathan Duri, 2023)
This research specifically examine the typology of pondok pesantren, both in Indonesia and Malaysia. This study is highly relevant because it provides an in-depth understanding of the typology of Islamic boarding schools in Indonesia and Malaysia, which can help in understanding the development and differences in culture and Islamic education in the two countries. The method used in this research is descriptive qualitative with the type of library research, using the Publish or Perish application as an instrument for identifying journal articles. At the initial stage, the number of articles obtained was 133, and they were reduced based on quality and novelty so that 85 articles remained. These articles were then filtered again based on the focus theme, leaving 44. These articles were read and eliminated again so that only 33 articles were obtained. The results of this study show that there are three typologies of Islamic boarding schools in Indonesia and Malaysia; salaf typology, modern typology, and convergence typology of salaf and modern.